Research and conservation of biodiversity in Peru: importance of using modern techniques and efficient administrative processes - von May, Rudolf (2012)
This commentary focuses on the importance that DNA sequence analysis has in biodiversity studies and the need for improving administrative procedures regarding biodiversity research in Peru. Given the rapid loss of biodiversity and natural resources in many areas of Peru, research aimed at identifying, characterizing, and describing biodiversity is a priority for developing appropriate conservation and mitigation strategies. For cur-rent and future research on Peruvian biodiversity and conservation, we emphasize the importance of using an integrative taxonomy approach, including the study of evolutionary processes associated with areas of high biodiversity and endemism. Additionally, it is essential that governmental institutions responsible for review-ing permit applications and research plans, focusing on biodiversity research in Peru, recognize and support studies that incorporate an integrative taxonomy approach. The use of modern techniques in the integrative taxonomy model in conjunction with efficient administrative procedures will be the best method for protecting Peruvian biodiversity.